Analysis of Changes In Risk Management Implementation At PT. ABC Based On ISO 31000:2018 - Adine Khairunisa Nadya; Sylvia Veronica Siregar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The implementation of a company's risk management is important because it can provide input for management to act preventively to prevent risk events that are often detrimental (downside risk). PT ABC as a subsidiary of the nickel mining company as Parent Company has transformed its risk management from partial to integrated based on ISO 31000: 2018. This change must be well prepared to avoid delays in the integration process because PT ABC has a project to develop the Industrial Estate and the RKEF (Rotary Kiln Electric Furnace) Smelter Development with a significant value so that preventing losses by carrying out risk mitigation efforts is important to implement. The purpose of this study is to comprehensively analyze changes in the application of risk management at PT ABC, evaluate the application of risk management adopted by the company, identify challenges faced by the company, and analyze the application of risk management to current business activities. The research method uses primary data through direct observation of existing change preparation practices and uses secondary data from related company data. The basis of the risk method used is the ISO 31000: 2018 guidelines. The results showed a significant impact in the integration of risk management adopted to be more comprehensive than the previous implementation. The risk management ntegration factor of the Parent Company and its subsidiaries has consequences for the sustainability of the program and budgeting in the RKAP, especially for improving the quality of risk management analysis through risk awareness programs. The implementation of PT ABC risk management in the RKEF smelter construction project identified 8 aspects of risk which include investment taxonomy (5 aspects), regulatory changes (1 aspect), and environment (1 aspect). Risk mitigation efforts have been carried out in the risk map from 1 aspect of high risk; 5 aspects of medium risk and to reduce the impact and probability that exists, namely: 3 risk aspects (from medium to high) and 5 risk aspects (from low to medium). This shows that there is a fairly good readiness to anticipate risks that have a negative impacts.